Winning arguments : what works and doesn't work in politics, the bedroom, the courtroom, and the classroom - Fish, Stanley Eugene (Harper, 2016)
"Stanley Fish, the notoriously brash and brilliant English and Law professor, has authored dozens of academic books on subjects ranging from Milton to freedom of speech. In 2011, Fish turned his eye to a more popular subject, the art of writing great sentences. His short, wise book How to Write a Sentence became an instant New York Times Bestseller and continues to be read by students and aspiring writers. Adam Haslet called the book, "deeper and more democratic than The Elements of Style." If great sentences are, in effect, performances at the highest level, Fish acts as a lively sportscaster giving the reader a blow-by-blow. In Winning Arguments, Fish employs this same wit and observational prowess as he guides readers through the "greatest hits" of rhetoric including landmark legal cases, arguments drawn from popular film and TV, and even Fish's own career. The success of books like Jay Heinrich's Thank You For Arguing demonstrate a clear audience for fun, intellectually nourishing books that make you feel just a little bit smarter for having read them. Like How to Write a Sentence, Winning Arguments will become a modern classic"--